Pengaruh Kebijakan Dividen, Ukuran Perusahaan, Kepemilikan Manajerial, dan Kebijakan Hutang Terhadap Nilai Perusahaan Pada Indeks Perusahaan LQ45 di BEI - Stefani Sindita Sari; Hwihanus Hwihanus (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
This study aims to identify the effect of dividend policy, company size and management ownership or debt policy on company value on Indonesia's LQ45 index (IDX). This research is also very quantitative using secondary data with an analytical descriptive approach. The analysis was carried out using Smart PLS 4 to carry out Discriminant Validity Test, Outer Model Collinearity Test, Reliability and Validity Test, and Path Coefficients Mean, STDEV, T Values, P Values Test. All companies whose shares were listed in the LQ45 index on the IDX during the period December 2021-December 2022 became the study population. Target sampling is used to select a sample of research participants. Based on the research, it was found that the IDX LQ45 company index is strongly influenced by various factors such as dividend policy, company size, management ownership, and debt policy.